ANALISIS IMPLEMENTASI PERPUSTAKAAN DESA BERBASIS INKLUSI SOSIAL DAN DAMPAKNYA BAGI MASYARAKAT: KAJIAN NARRATIVE LITERATURE REVIEW - Supriyatno, Hary; Margono, Hendro (IAIN Ponorogo, 2025)
Social inclusion is one of the priority programs initiated by the National Library of Indonesia, serving as a strategic effort to improve the quality of life and community welfare through the transformation of the library’s role. Libraries are no longer limited to managing and providing collections but are required to become centers for access to information sources and community empowerment activities. Library transformation can be realized through the provision of appropriate infrastructure, facilities, human resources, and technology that meet community needs. The implementation of social inclusion in libraries requires a reference model, particularly for village libraries that need an applicable and contextually relevant framework. The study aims to identify conceptual models for implementing social inclusion in village libraries and to examine the impacts synthesized from existing literature, so that they may be adapted or adopted by other libraries to enhance the community‘s quality of life and welfare. The research employs a narrative literature review, conducted on four peer-reviewed articles discussing social inclusion in village libraries obtained through Publish or Perish and selected based on journal accreditation and citation impact. The analysis reveals four key elements in the implementation of social inclusion in village libraries: (1) collections aligned with community needs, (2) user-oriented services, (3) competent human resources, and (4) strong collaborative partnerships. The impacts synthesized from the literature include accelerated village development, enhanced community competence and welfare, and the transformation of libraries into centers of information and productive community engagement. The main challenges in implementation include uneven utilization of information technology, dependency upon external cooperation programs, and limited community participation.